Analisis Hukum Pidana terhadap Kasus Korupsi Pengadaan Barang dan Jasa : Studi Kasus Benih Bawang Merah Malaka - Antonius Candra Mudakh; Debi F. Ng Fallo; Rudepel Petrus Leo (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the criminal law liability of the perpetrators in the case of corruption in the procurement of red onion seeds in Malaka Regency based on four decisions of the Kupang District Court: Decision of the KUPANG District Court Number 39 / Pid.Sus-TPK / 2023 / PN Kpg, Decision of the KUPANG District Court Number 40 / Pid.Sus-TPK / 2023 / PN Kpg, Decision of the KUPANG District Court Number 41 / Pid.Sus-TPK / 2023 / PN Kpg, and Decision of the KUPANG District Court Number 42 / Pid.Sus-TPK / 2023 / PN Kpg. This study uses a normative legal approach supported by empirical data through interviews with advocates, prosecutors, and judges. The results of the study indicate that the elements in Article 3 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 has been cumulatively fulfilled in this case, namely the abuse of authority, state financial losses, and benefits for oneself or others. The application of the article to all defendants is considered legally valid, but in practice it does not fully reflect substantive justice because the roles and levels of involvement are not distinguished proportionally. The judge's decision and the prosecutor's indictment are considered consistent in normative aspects,but still leave challenges in terms of assessing the burden of proof and classification of criminal responsibility. This finding recommends the importance of evaluating the criminalization system, strengthening the capacity of procurement officials, and updating policies that distinguish between administrative errors and criminal acts of corruption.